Size-age structure of oyster Crassostrea gigas in the Losos Bight (Aniva Bay, Okhotsk Sea) - A. Ch. Kim; R. T. Gon (Известия ТИНРО, 2020)
Data on age structure, shell size (height, length, thickness) and weight of oyster Crassostrea gigas in the Losos Bight (Aniva Bay, Okhotsk Sea) are presented on results of the surveys conducted in 2018 and 2019. The size-age key for the total weight is plotted. The size-age structure is compared with oysters from other habitats.